PERTANGGUNGJAWABAN NABI YEHEZKIEL SEBAGAI PENJAGA UMAT ISRAEL - Sostenis Nggebu; Fenius Gulo; Joko Susilo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
The problem of this article discusses the critical function of the prophet Ezekiel's control over the spirituality of the Israelites in Babylon. He carried out this vital role so that the life of the Israelites' faith returned to the right path. The method used in this study is a biblical textual study method. The result shows that Ezekiel carried out God's mandate with sincerity and sincerity as the guardian of the people of Israel. He was well aware that God himself would hold him accountable. In the land of exile, Ezekiel faithfully carried out his duty as a guardian of Israel. He rebuked those who deviated from the word of God and those who obeyed the word of God he comforted. In addition, he also conveyed the message of hope that God would act according to His sovereignty to return the Israelites from the land of exile.